Resilience of Social-Ecological Systems: At the Limits of Hegemonic Masculinity - Mukoni Manuku (Springer, Cham, 2022)
A key challenge of the Anthropocene era is to advance human development without crossing ecological thresholds or undermining critical ecological services. The purpose of this chapter is to show that we cannot hope for social-ecological resilience, viability, and stasis if the underlying value systems of society, especially hegemonic masculinity tendencies, remain untouched. The chapter underscores that hegemonic masculinity tendencies have a larger ecological footprint that is responsible for the emergence of many social-ecological risks and emergencies, which cause certain dynamics of vulnerability, insecurity, and crises for both social and ecological systems. The chapter observes that although attempts have been made to integrate a gender perspective into social-ecological resilience analysis, much of this research has focused on the understanding of the interdependent relations between social-ecological systems and gender. This analysis transcends such paradigms to argue that it is not enough. What is needed is not a mere incorporation of gender analysis but the transformation of hegemonic masculinity value systems given its significant influence on socio-ecological resilience. Furthermore, the analysis shows that it is the same hegemonic masculinity tendencies that contribute to the incapacity of society to manage risk dynamics and reduce vulnerability. The analysis refers to Raewyn Connell’s (1987) theory to show how hegemonic masculinity acts as a structural and systemic driver of social-ecological systems insecurity, vulnerability, and risks. The chapter proposes a shift to a gender transformative paradigm in social-ecological resilience that targets hegemonic masculinity.